The Context-Dependency of the Experience of Auditory Succession and Prospects for Embodying Philosophical Models of Temporal Experience - Kon, Maria (Empirical Musicology Review, 2015)
Recent philosophical work on temporal experience offers generic models that are often assumed to apply to all sensory modalities.  We show that the models serve as broad frameworks in which different aspects of cognitive science can be slotted and, thus, are beneficial to furthering research programs in embodied music cognition.  Here we discuss a particular feature of temporal experience that plays a key role in such philosophical work: a distinction between the experience of succession and the mere succession of experiences.  We question the presupposition that there is such an evident, clear distinction and suggest that, instead, it is context-dependent.  After suggesting a way to modify the philosophical models of temporal experience to accommodate this context-dependency, we illustrate that these models can fruitfully incorporate research programs in embodied musical cognition.  To do so we supplement a philosophical model with Godøy’s recent work that links bodily movement with musical perception.  The Godøy-informed model is shown to facilitate novel hypotheses, refine our general notion of context-dependency and point towards possible extensions.